PENGEMBANGAN BUKU KONSEP MATEMATIKA BASIS PROBLEM-BASED LEARNING (PBL) PADA POKOK BAHASAN ALJABAR - Nengsi Maswi; Syafri, Fatrima Santri (Universitas Islam Nusantara, 2026)
This.study.aims.to.produce.a.Problem.Based.Learning. (PBL) .based.mathematics.concept book.on.the.topic.of.algebra.to.improve students’ understanding of algebraic operations. The.method used-is-Research-and-Development- (R&D) -with-the-Plomp-model, -which-consists of three main phases: initial investigation, prototype-development, -and-assessment. The-validation-results-show that the book falls into-the- “very-valid” -category-with scores-of 86.67% from material experts, 93.33% from media experts, and 90% from language experts. Student responses-indicate-a-practicality level of 72.72% (practical). Meanwhile, the learning outcomes show an average score of 71.18, indicating the effectiveness of the book in helping students understand algebraic concepts. Thus, the PBL-based mathematics concept book developed is declared valid, practical, and effective as an alternative teaching material for algebra learning at the junior high school level.